Penerapan Metode User Centered Design Dalam Perancangan Sistem Informasi Kasir - Purnama, Charina Ayu; Mariana, Novita (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2023)
Micro, Small, and Medium Enterprises, known as UMKM, is a business that is carried out privately or individually. MSMEs are businesses that are favored and carried out by some entrepreneurs. One of them is Agung Tirta, which is an MSME in the field of drinking water that provides various types and brands of drinking water. With an average sales of around 1000 transactions each month with an average income of twelve million rupiahs per month. With a large number of transactions, Agung Tirta MSMEs experience difficulties in processing transactions and data processing as well as reports on purchase results so errors often occur when using the cashier manually. Therefore a cashier information system is needed to assist with this problem. To design a cashier information system by applying the User Centered Design (UCD) method, which is a method that prioritizes user needs and convenience, with the user being the center of the system development process which is the concept of UCD, the purpose of the system is based on a design from start to finish. Using the UCD method will produce a cashier information system that suits the needs and desires of the user or users.Keyword: Cashier Information System; Micro small and Medium Enterprises; User Centered DesignÂ Abstrak Agung Tirta yang merupakan UMKM dibidang air minum yang menyediakan beraneka jenis dan merk air minum. Dengan rata-rata penjualan sekitar 1000 transaksi setiap bulannya dengan pendapatan rata-rata perbulan dua belas juta rupiah. Dengan banyaknya jumlah transaksi maka UMKM Agung Tirta mengalami kesulitan dalam proses transaksi dan pengolahan data juga laporan hasil pembelian sehingga sering terjadinya kesalahan saat menggunakan kasir secara manual. Oleh karena itu sistem informasi kasir dibutuhkan untuk membantu dalam permasalahan tersebut. Untuk merancang sistem informasi kasir dengan menerapkan metode User Centered Design (UCD) adalah sebuah metode yang mengutamakan kebutuhan dan kenyamanan user, dengan user dijadikan sebagai pusat dari proses pengembangan sistem yang merupakan konsep dari UCD, tujuan dari sistem didasari dari perancangan dari awal hingga akhir. Dengan menggunakan metode UCD akan menghasilkan sistem informasi kasir yang meliputi daftar stok barang, laporan penjualan dan menghitung laba keuntungan.